Unlocking financial data - Alexandru Chistruga (EURINT)
The current research will concentrate on a legislative proposal that is awaiting approval, namely the proposal for a regulation of the European Parliament and of the Council on a Framework for Financial Data Access. The proposed legislation seeks to establish rules governing the use, sharing, and access of certain categories of customer data in financial services, such as mortgage credit agreements, loans, investments in financial instruments, or pension rights. We understand the European Union's desire to establish a framework for access to financial data, especially since access to data would allow businesses to offer tailored products to customers based on the information they collect, but the regulation, at least in its current form, entails a number of obvious risks. For instance, investors specializing in recovering non-performing loans, also referred to as vulture funds, would obtain a plethora of information, facilitating the identification of debts suitable for effective enforcement. Therefore, the proposed regulation appears to be a lifeline for vulture funds, increasing their efficiency rather than eliminating them, even though, as we will show, their practices may be regarded as unethical.